Efficiency of two protocols for maxillary molar intrusion with mini-implants - Juliana Volpato Curi Paccini; Flávio Augusto Cotrim-Ferreira; Flávio Vellini Ferreira; Karina Maria Salvatore de Freitas; Rodrigo Hermont Cançado; Fabrício Pinelli Valarelli
ABSTRACT Objective: The aim of this study was to compare the efficiency of two protocols for maxillary molar intrusion with two or three mini-implants. Methods: Twenty five maxillary first molars extruded for loss of their antagonists in adult subjects were selected. The sample was divided into two groups, according to the intrusion protocol with two or three mini-implants. Group 1 consisted of 15 molars that were intruded by two mini-implants. Group 2 consisted of 10 molars intruded by three mini-implants. Changes with treatment were analyzed in lateral cephalograms at the beginning and at the end of intrusion of maxillary molars. Results: Results showed that there was no difference in efficiency for the two intrusion protocols. It was concluded that extruded maxillary molars can be intruded with two or three mini-implants with similar efficiency.